Allerjik konjonktivit tedavisinde lodoksamid ve otopatadinin etkinliğinin karşılaştırılması ve gözyaşı sICAM-1 düzeyleri üzerine etkilerinin değerlendirilmesi - (:unkn) unknown (My University, 2003)
Amaç: Mevsimsel ve pereneal konjonktivit tedavisinde olopatadin ve lodoksamidin etkin-liğinin karşılaştırılması ve gözyaşı solubl intersellüler adezyon molekülü -l (sICAM-1) düzeyleri üzerine etkilerinin araştırılması. Gereç ve Yöntem: Bu prospektif randomize çalışmaya aktif mevsimsel veya pereneal allerjik konjonktiviti olan 19 hasta ve 8 sağlıklı kontrol dahil edildi. Tedavi öncesi, hastaların allerjik konjonktivit semptom ve bulguları değerlendirildi, hastalardan ve kontrollerden gözyaşı örnekleri toplandı. Hastalar randomize olarak topikal %0.1'lik olopatadin 2x1 damla/gün (n=9) veya %0.1'lik lodoksamid 4x1 damla/gün (n=10) tedavisi almak üzere iki gruba ayrıldı. Tedavinin 3., 7., 14. ve 30.günlerinde hastaların klinik değerlendirilmesi tekrarlandı ve 14.günde hastalardan tekrar gözyaşı toplandı. Gözyaşı sICAM-1 düzeyi ELISA yöntemiyle tayin edildi. Bulgular: Olopatadin tedavi grubunda, tüm kontrol muayenelerinde klinik semptom ve bulgu skorunda tedavi öncesine göre belirgin iyileşme saptandı (p<0.05). Lodoksamid tedavi grubunda, 3. gün dışındaki diğer kontrollerde anlamlı klinik iyileşme olduğu görüldü (p<0.05). Tedavinin 3. gününde olopatadin tedavisinin lodoksamide göre semptom (p=0.03) ve bulgular-da (p=0.02) daha fazla düzelme sağladığı saptandı. Diğer kontrollerde (7., 14. ve 30. gün) klinik semptom ve bulgularda bazal muayeneye göre değişim miktarının tedavi grupları arasında farklılık göstermediği görüldü. Allerjik konjonktivitli hastalarların gözyaşı sICAM-1 düzeyleri kontrol grubundan istatistiksel olarak anlamlı farklılık göstermemekteydi. Her iki tedavi grubunda, tedavi öncesi ve tedavi sonrası gözyaşı sICAM-1 düzeyleri arasında anlamlı farklılık tespit edilmedi. Sonuç: Allerjik konjonktivit tedavisinde olopatadin ve lodoksamid eşit etkinliğe ve güvenilirliğe sahiptir ancak olopatadinin etkisi daha erken başlamaktadır. Her iki antiallerjik tedavinin gözyaşı sIC AM-1 düzeylerine etkisi olmadığı görülmüştür.

Purpose: To compare the therapeutic efficacy of olopatadine and lodoxamide in seasonal and perennial allergic conjunctivitis and to investigate the effect of anti-allergic treatment on tear levels of sICAM-1. Methods: Nineteen patients diagnosed as active seasonal or perennial allergic conjunctivi-tis and 8 control subjects particitated in this prospective, randomized study. The ocular symptoms and signs of allergic conjunctivitis were evaluated and tear samples were collected from allergic conjunctivitis patients and control subjects. Patients with allergic conjunctivitis were randomized into two groups to receive either topical 0.1% olopatadine bid (n=9) or 0.1% lodoxamide qid (n=10). Patients were evaluated at days 3, 7, 14 and 30 during the treatment phase. Tear samples were recollected at day 14. Tear levels of sICAM-1 were assesed by ELI-SA.3 Results: In olopatadine treatment group, significant improvements from baseline in clinical signs and symptoms were observed in all visits during the treatment phase (p<0.05). In lodoxa-mide treatment group with the exception of day 3, significant improvements were observed in other control visits (p<0.05). Olopatadine treatment produced significantly greater improvement in clinical symptoms (p=0.03) and signs (p=0.02) than lodoxamide treatment at day 3. There were no significant among-group differences in the change from baseline in clinical signs and symptoms at day 7,14 and 30. Tear sICAM-1 levels in patients with allergic conjunctivitis did not significantly differ from that of controls. No statistically significant change was observed between the pre and post treatment levels of sICAM-1 in either treatment group. Conclusion: While both olopatadine and lodoxamide are found to be effective in the treatment of allergic conjunctivitis, olopatadine appears to have an earlier onset of action. Neither anti-allergic treatment caused a significant change in sICAM-1 tear levels.
Comparison of the efficacy of lodoxamide and olopatadine in the treatment of allergic conjunctivitis and evaluation of their effect on tear levels of sICAM-1
Keywords: Alerji; Hematoloji; Pediatri